Imidazoline Receptor Agonists for Managing Hypertension May Hold Promise for Treatment of Intracerebral Hemorrhage - Mahmoudi, J.; Majdi, A.; Lattanzi, S.; Di Napoli, M.; Bershad, E.M.; Rodrigues, C.M.P.; Divani, A.A. (Current Molecular Medicine, 2018)
Intracerebral hemorrhage (ICH), which accounts for 10% of all strokes, leads to higher morbidity and mortality compared with other stroke subtypes. Hypertension has been recognized as a major risk factor for ICH. Current antihypertensive options have not been fully effective for either prevention of ICH or ameliorating its complications. Therefore, attempts should be made to use novel antihypertensive medications for more effective management of blood pressure (BP) in the acute phase of ICH. Imidazoline receptor (IR) agonists can potentially be effective agents for BP control with the adjunctive ability to attenuate post-ICH brain injury. IR agonists render neuroprotective effects including inhibition of inflammatory reactions, apoptotic cell death, excitotoxicity, and brain edema. Given these properties, the present review aims to focus on the application of IR agonists for managing BP in ICH patients.
Keywords: inflammation